Jonas Kaufmann, My Italy RAI National Symphony Orchestra - Leoncavallo, Ruggiero 1858-1919; Dalla, Lucio; Valente, Nicola; Rota, Nino 1911-1979; De Curtis, Ernesto 1875-1937; Gastaldon, Stanislao 1861-1939; De Curtis, Ernesto 1875-1937; Cottrau, Guillaume Louis 1797-1847; De Crescenzo, Vincenzo 1875-1964; Musumarra, Romano; Cardillo, S.; D'Anzi, Giovanni 1906-1974 (A production of Sony Classical and ZDF in cooperation with C Major Entertainment, 2016)
In the concert-documentary My Italy, Jonas Kaufmann presents a love song to the culture that has so greatly inspired him. Select songs recorded during a concert in Turin (among them Caruso, Mattinata, Parla più piano, and Core 'ngrato) are interspersed with interviews in which he describes this love affair of long date ... immersed since childhood in Italian culture, he is the country's adopted son, and feels a special connection with the Italian spirit and the characteristic flavors of its music. Photo: Jonas Kaufmann © Gregor Hohenberg / Sony Music
Keywords: concert; Internet videos